2020
DOI: 10.1155/2020/7272960
|View full text |Cite
|
Sign up to set email alerts
|

A Three Protein-Coding Gene Prognostic Model Predicts Overall Survival in Bladder Cancer Patients

Abstract: Bladder cancer (BLCA) is the most common urinary tract tumor and is the 11th most malignant cancer worldwide. With the development of in-depth multisystem sequencing, an increasing number of prognostic molecular markers have been identified. In this study, we focused on the role of protein-coding gene methylation in the prognosis of BLCA. We downloaded BLCA clinical and methylation data from The Cancer Genome Atlas (TCGA) database and used this information to identify differentially methylated genes and constr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…GAL 1 R DNA methylation is among the most epigenetic molecular alterations in endometrial cancer; this methylation indicates malignancy with a high degree of sensitivity and specificity [ 208 ]. The methylation of the GAL 1 R gene in bladder cancer has been involved in the prognosis of the disease, but the role played by the galaninergic system in this cancer is currently unknown [ 209 ].…”
Section: The Galaninergic System and Cancermentioning
confidence: 99%
“…GAL 1 R DNA methylation is among the most epigenetic molecular alterations in endometrial cancer; this methylation indicates malignancy with a high degree of sensitivity and specificity [ 208 ]. The methylation of the GAL 1 R gene in bladder cancer has been involved in the prognosis of the disease, but the role played by the galaninergic system in this cancer is currently unknown [ 209 ].…”
Section: The Galaninergic System and Cancermentioning
confidence: 99%
“…Recently, ZNF382 was reported as a component of an epigenetic signature that predicts the survival of laryngeal squamous cell carcinoma [ 53 ]. Moreover, with two other protein-coding genes, ZNF382 forms a prognostic signature that robustly predicts the outcome of bladder cancer patients [ 54 ]. Distinct methylation pattern of ZNF382 promoter might serve as a biomarker in pancreatic ductal carcinoma [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…High levels of ANLN contributed to the poor prognosis of anthracycline-based chemotherapy in breast cancer patients [ 53 , 54 ]. A three protein-coding genes prognostic model including SMCHD1 predicts overall survival in bladder cancer patients [ 55 ]. Univariate and multivariate survival analysis showed that high expression of HAUS3 was an independent prognostic factor for the dismal outcome of overall survival of HCC patients [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…A three protein-coding genes prognostic model including SMCHD1 predicts overall survival in bladder cancer patients [ 55 ]. Univariate and multivariate survival analysis showed that high expression of HAUS3 was an independent prognostic factor for the dismal outcome of overall survival of HCC patients [ 55 ]. High expression of HAUS3 is also associated with poor prognosis and HCC progression [ 56 ].…”
Section: Discussionmentioning
confidence: 99%